Médenine : Lancement du projet "yati nature" pour la protection de la plage de Djerba Midoun (Agence Tunis Afrique Presse, 2026)
Keywords: Littoraux -- Djerba

Biodiversité marine à Djerba : 287 000 $ mobilisés pour renforcer la conservation de Ras Rmel (Webmanagercenter, 2025)
Un accord de financement de cinq ans a été récemment signé entre l’Agence de Protection et d’Aménagement du Littoral (APAL), l’ONG locale AJEM (Association Jlij pour l’Environnement Marin) et le Fonds &qout;The MedFund&qout; pour soutenir la cogestion de la zone de protection marine &qout;Jerba Ras Rmel&qout;, a…
Keywords: Littoraux -- Djerba

Projet de ceinture verte - Marrakchi, Abdulwahab (Colloque environnement et érosions littorales à Djerba, 1980)
Keywords: Géologie -- Djerba; Littoraux -- Djerba

Approche explicative de l'évolution morphogénétique du littoral et des ploges à Djerba - Yamoun, Messaoud (Colloque environnement et érosions littorales à Djerba, 1980)
Keywords: Géologie -- Djerba; Littoraux -- Djerba

Note sur les activités d’extraction de la pierre et du sable à Djerba - Yamoun, Messaoud (Colloque environnement et érosions littorales à Djerba, 1980)
Keywords: Géologie -- Djerba; Littoraux -- Djerba

Formes et évolutions actuelles du littoral de Djerba-Zarzis - Ben Ouezdou, Hedi; Rebhi, Ameur (Colloque environnement et érosions littorales à Djerba, 1980)
Keywords: Géologie -- Djerba; Littoraux -- Djerba

Shawāṭāʾ Jazīrat Jarba bayn naswha al-aḥyā ʾ al-mukathaf wa surʿa al-tadhūr al-Khaṭīr lil-muḥīṭ : al-muʿādalla al-mustaḥīl - Bourgou, Mongi (al-Jazira, 1996)
Keywords: Littoraux -- Djerba

Alerte à Djerba : Outrage au littoral - Bouabid, Naceur (Turess, 2010)
Keywords: Littoraux -- Djerba

Formations littorales et estuaires de la Syrte Mineure (Golfe de Gabès). - Seurat, Gaston Léon (Bulletin de la Station Océanographique de Salammbo, 1934)
La petite Syrte est avant tout remarquable par ses cotes basses,ses grands estuaires et les sebkha qui la bordent; ces conditions particulieres,jointes a l'existence des grands chotts du sud Algero-Tunisiens n'avaient pas manque de frapper les anciens,qui nous ont laisse la legende du Triton.
Keywords: Littoraux -- Djerba

La protection du littoral tunisien contre l’érosion marine et la protection des zones humides - Zine el Abidine, Hayet; Tebib, Jamel (Annales de l'Equipement)
Keywords: Littoraux -- Djerba

L'île de Djerba
Keywords: Littoraux -- Djerba

Is Littoralization Reconfiguring the Omani Territory? - Mokhtar, Belgacem (Regionalizing Oman: Political, Economic and Social Dynamics, 2013)
Keywords: Littoraux -- Djerba

Evolution et morphodynamique des îles barrières et des flèches littorales associées à des embouchures microtidales dans le Sud-Est tunisien - Masmoudi Kchaou, Sameh; Yaïch, Chokri; Yamoun, Messaoud (Bulletin de l’Institut Scientifique, 2005)
Keywords: Littoraux -- Djerba

Oman and the West : state formation in Oman since 1920 - Owtram, Francis (London School of Economics and Political Science, 1999)
This thesis analyses the external and internal influences on the process of state formation in Oman since 1920 and places this process in comparative perspective with the other states of the Gulf Cooperation Council. It considers the extent to which the concepts of informal empire and collaboration are useful in analysing the relationship between Oman, Britain and the United States. The theoretical framework is the historical materialist paradigm of International Relations. State formation in Oman since 1920 is examined in a historical narrative structured by three themes: (1) the international context of Western involvement, (2) the development of Western strategic interests in Oman and (3) their economic, social and political impact on Oman. The incorporation of the Arabian littoral into the security sphere of the British empire in India separated the Imamate in the mountainous interior of Oman from the British-backed Sultans in Muscat. This culminated in the Treaty of Sib in 1920 following which the government of the Sultanate was restructured by British officials. The discovery of oil in Bahrain in 1932 marked a new phase in the incorporation of the Arabian peninsula into the capitalist world-system. In south-east Arabia this led to the occupation of the interior in 1955 by the British-supported forces of Sa'id bin Taimur. The coup of 1970 in which Qabus became Sultan allowed the development of a pro-Western rentier state and the defeat of the rebels in Dhofar. British imperial withdrawal from the region was completed with the relinquishment of its bases in the Sultanate of Oman in 1977. The development of a strategic relationship between Oman and the United States in the 1980s enhanced American military deployment during the Kuwait crisis of 1990-1991. In the aftermath of this conflict Oman faces the challenge of political development in an environment of diminishing oil reserves.
Keywords: Littoraux -- Djerba

Remarques sur les causes et remède de l'érosion des plages à Djerba - Paskoff, Roland (Colloque environnement et érosions littorales à Djerba, 1980)
Keywords: Géologie -- Djerba; Littoraux -- Djerba

Stabilité des plages-conception des plages artificielles: Etude et modélisation. Application à la côte Est de Jerba - Mejri Chtioui, Imen (Ecole Nationale d'Ingénieurs de Tunis)
Keywords: Littoraux -- Djerba

Caractéristiques environnementales et dynamique littorale de la plage d’Aghir à Jerba - Zekri Harrabi, Faten (Faculté Des Sciences de Sfax, 2005)
Keywords: Littoraux -- Djerba

Zone sensible littorale de Ras Remel à Jerba - Scet (Agence de Protection et d’Aménagement du Littoral, 1999)
Keywords: Littoraux -- Djerba

L’érosion des plages dans le sud tunisien : exemples à Jerba (côtes Est et Sud-Est) et à Zarzis - Miossec, Jean-Marie; Paskoff, Roland (Revue tunisienne de géographie, 1979)
Keywords: Littoraux -- Djerba

Etude d’un modèle de sédimentation littorale actuelle active: Cas de la flèche littorale Ras R’mel au nord de Jerba - Khlifi, Imed (Faculté Des Sciences de Sfax, 2005)
Keywords: Littoraux -- Djerba

Les sédiments du littoral et leur mobilité : Introduction à l'étude des mécanismes sédimentaires - Le Nindre, Y. M.; Howa, H. (Éditions BRGM, 1999)
Keywords: Littoraux -- Djerba

Série d’études non publiées et relatives à différents aspects du paysage de Djerba - CNERP; Equipe franco-tunisienne du paysage littoral (Association pour la Sauvegarde de l’île de Djerba, 1979)
Keywords: Littoraux -- Djerba

Le littoral de Djerba entre nature et société - Bourgou, Mongi (Colloque international Insularité, langue, mémoire, identité, 2014)
Keywords: Littoraux -- Djerba

Peut-on et doit-on lutter contre l’érosion des plages : Le cas de Jerba ? - Bourgou, Mongi (11ème Colloque Béchir Tellili Les activités maritimes à l’île de Jerba et en méditerranée durant les siècles, 2012)
Keywords: Littoraux -- Djerba

Milieu littoral et aménagement : le cas du littoral nord oriental de la presqu’île de Zarzis - Bourgou, Mongi (Revue tunisienne de géographie, 1995)
Keywords: Littoraux -- Djerba

Lagoonal sand smelts (atherina lagunaea, teleostei, atherinidae) inhabit marine shallow waters of the coasts of Djerba island (Tunisia) - Bouriga, Nawzet; Selmi, S.; Aurelle, D.; Barthelemy, R.; Quignard, Jean-Pierre; Trabelsi, M.; Faure, E. (Bulletin de l’Institut National des Sciences et Technologies de la Mer, 2009)
Keywords: Littoraux -- Djerba

Automatic Measurement of Shoreline Change on Djerba Island of Tunisia - Bouchahma, Majed; Yan, Wanglin (Computer and Information Science, 2012)
Keywords: Littoraux -- Djerba

Post-Mortem Onshore Transportation of Epiphytic Foraminifera: Recent Example from the Tunisian Coastline - Davaud, Eric; Septfontaine, Michel (Journal of Sedimentary Research, 1995)
The barrier island system that connects Jerba Island to the Tunisian coastline is composed mainly of carbonate bioclastic sands. Well-preserved tests of dead epiphytic foraminifera are abundant on the foreshore and backshore, but they are scattered and poorly preserved on the shoreface, where very fine sand-size eolian quartz, peloids, and broken bioclasts are the main components. The reason for this paradoxical pattern is that most epiphytic foraminifera are very easily removed as suspended load by storm-generated currents and concentrated on beaches, washover fans, and small eolian dunes, kilometers avay from their original life environment. Similar bioaccumulations are common in the fossil record and have often been interpreted incorrectly as prolific biocoenoses.
Keywords: Littoraux -- Djerba

Origine de la minéralisation des eaux de la nappe phréatique de l’île de Djerba (Tunisie) : Application des méthodes hydrochimique et Isotopique - Trabelsi, Rim; Zouari, Kamel (Association Internationale des Hydrogéologues, 2012)
Keywords: Littoraux -- Djerba

Les littoraux enjeux et dynamiques - Bourgou, Mongi; Miossec, Jean-Marie (Presses universitaires de France, 2010)
Keywords: Littoraux -- Djerba

Etude de la dynamique sédimentaire dans la frange littorale de Jerba Ras Taguermess - Ras Marmour - Atoui, Abdelfattah (Ecole Nationale d'Ingénieurs de Tunis, 2009)
Keywords: Littoraux -- Djerba

Formes et évolution actuelle du littoral de Jerba Zarzis - Assidje (Association pour la Sauvegarde de l’île de Djerba, 1980)
Keywords: Littoraux -- Djerba

Colloque environnement et érosion littorale à Djerba, 19 et 20 janvier 1980 - Assidje; Office national du tourisme tunisien; Association des géographes tunisiens (Document, 1980)
Keywords: Géologie -- Djerba; Littoraux -- Djerba

Note sur les activités d’extraction de la pierre et du sable à Jerba - Yamoun, Messaoud (Association pour la Sauvegarde de l’île de Djerba, 1979)
Keywords: Géologie -- Djerba; Littoraux -- Djerba

Nourishment of a barred nearshore: jerba, Tunis - Boczar-Karakiewicz, B.; Romanczyk, W.; Long, Bernard; Bona, J. L. (Solving Coastal Conundrums, 2002)
A project to reconstruct 9~km of sandy beaches located in the north-eastern part of Jerba Island (Tunisia) is presented. The beaches face the Mediterranean Sea, and multiple offshore sand bars are a common feature in this area. The visible and underwater parts of the beaches have been eroded by sand losses, shoreline retreats, recurrent flooding, steepened nearshore profiles and continuosly decreased volume of offshore sand bars. Erosion and degradation of the coastal dunes have resulted from recreational developments in the area. Earlier `hard' protection measures implemented, such as seawalls, ripraps, etc., failed. Our project proposes a `soft' protection method that involves supplying the lacking sediment to 'strategic' places in the nearshore zones for the restoration of their wave-dominated dynamic equilibrium. Our recommendations for the project are based on historical data, observations, field measurements and numerical simulations, using a mathematical model of wave-seabed interactions (Boczar-Karakiewicz et al. 1987), with initial data provided by field measurements of waves, currents and morphology. The model predicts the formation of longshore bars and their site-specific dynamics in response to sequences of storm events in the local wave climate, while reproducing the observed quasi-periodicity of beach erosion and recovery. The conclusions of the project recommend the nourishment of two offshore bars and reconstruction of the beaches to a width of some 70 m (their pre-erosion state). The increased volume of the nourished bars will assure protection and stable conditions for the reconstructed beaches and prevent flooding. Boczar-Karakiewicz B., Bona J.L. and Cohen D.L., 1987. Interaction of shallow-water waves and bottom topography. In: Dynamical problems in continuum physics, mathematics and its application, J.L. Bona, C. Dafermos, J. Erickson & D. Kinderlehrer, editors, Springer-Verlag, New York, IMA Series in Mathematics and its Applications, 4, 131-176.
Keywords: Littoraux -- Djerba

Water renewal in the Boughrara lagoon (Tunisia, central Mediterranean Sea) under tidal forcing - Atoui, Abdelfattah; Smeti, Houssem; Sammari, Cherif; Ben Ismail, Sana (Estuarine, Coastal and Shelf Science, 2020)
Keywords: Littoraux -- Djerba

Contingent valuation analysis of willingness to pay for beach erosion control through the stabiplage technique: A study in Djerba (Tunisia) - Dribek, Abderraouf; Voltaire, Louinord (Marine Policy, 2017)
Keywords: Littoraux -- Djerba

étude générale pour la protection du littoral tunisien contre l’érosion marine - littoral nord-est de Jerba. Avant-projet sommaire - Apal (Studi-Sogreah-groupe canadien, 2001)
Keywords: Littoraux -- Djerba

Gestion de zone sensible. La presqu’île de Bin Ouediane - Apal (Comete Engineering, 2000)
Keywords: Littoraux -- Djerba

Étude de la gestion de la zone sensible de Ras Remel à Jerba. Résumé du rapport de phase 1 - Apal (SCET-Tunisie, 1999)
Keywords: Littoraux -- Djerba

Abundance and biomass of the ciliate community during a spring cruise in the Gulf of Gabes (Eastern Mediterranean Sea, Tunisia) - Aleya, Lotfi; Hannachi, Imen; Drira, Zaher; Hassen, Malika; Hamza, Asma; Ayadi, Habib; Bouain, Abderrahman (Acta Protozoologica, 2008)
We studied the spring spatial distribution of the ciliate community coupled with environmental factors along the coast and in the open sea at 30 stations sampled (between 27 May and 9 June 2006) in the Gulf of Gabes (Tunisia, Eastern Mediterranean Sea). A total of 61 taxa belonging to 36 genera and 5 taxonomic classes were identified. The ciliate assemblage was numerically dominated by spirotrichs (86% of total ciliates). This group is largely dominated by the choreotrichs (92%) among which tintinnids represented 99%. The total ciliates abundance showed a gradual decrease from the coastal area to the open sea and an increase from the surface to the bottom. The maximum abundance (400 cells l-1) and biomass (6.29 µgC l-1) were found in station 27, close to Djerba Island. The tinitinnid Rhabdonella spiralis was cosmopolitan, being found almost at every station and at each depth, while other taxa may be exclusive to the neritic area, others to the open sea area. The distribution of species in the Gulf of Gabes seemed most likely influenced by the combined effects of hydrographic conditions, zooplankton predation and urban interferences.
Keywords: Littoraux -- Djerba